VIRTUAL ASSETS AND VIRTUAL ASSET SERVICE PROVIDERS: REQUIREMENTS OF INTERNATIONAL AML/CFT/CPF STANDARDS (World Bulletin of Management and Law, 2023)
The development of modern trends in the use of virtual assets for money laundering and the requirements of international standards for the latest technologies are being studied. In the article, taking into account the comparative legal analysis of the FATF Recommendations and international conventions that regulate the activities of virtual asset service providers and forensic activities, the features of the national approaches of states to this activity are identified